The relationship between the different oncological treatments and the benefits of physical activity: A literature review (Research, Society and Development, 2026)
Introduction: Cancer is a disease of great interest for different professionals. In this sense, during cancer treatment different ways are sought to reduce the unfavorable effects of this disease. Objective: To analyze the scientific production related to physical activity during and after cancer therapy and its benefits for the individual. Method: Narrative literature review, using articles obtained from the National Library of Medicine (PubMed), Scientific Electronic Library Online (SciELO), Virtual Health Library (VHL) and Google Scholar databases of the National Institutes of Health for data collection, using keywords related to "physical activity", "sport", "physical exercise" and "cancer treatment". Results: 20 articles were evaluated and it was possible to identify that physical activity during and after treatment can bring benefits to patients. Conclusion: Despite the positive results demonstrated in the research, further studies are still necessary, especially in relation to the most appropriate physical exercise and its intensity.